Role and Political Strategy of Women Village Heads in Development of Rural Politics - Ismail, Ashari; Torro, Supriadi; Umar, Firman; Irwansyah, Idham; Hardiyanti Arhas, Sitti (KnE Social Sciences, 2024)
The current study is a research on the political roles and strategies of women village heads in rural political development. The study was conducted in Parenreng Village, Pangkep, South Sulawesi Indonesia. Women undeniably, play a strategic role in every area of village political development. Village women’s work is not just “complementary development,” but also the subject of a role that has “control and power.” The research conceptualization used is structural-functional theory while the method used is descriptive qualitative approach. The research findings show that the work and strategies of women village heads are: (a) Village political development, carried out directly, with empathy for humanizing; (b) Putting the interests of a small and modest society above the interests of the advanced people; and (c) Urgent and strategic development of rural infrastructure. Economic empowerment must always be encouraged with the principle of togetherness and solidarity. The progress and political strategies of women village heads thus show that women play a crucial role in the political role of rural development. Keywords: female village heads and rural politics